2023
DOI: 10.3390/ijms24065628
|View full text |Cite
|
Sign up to set email alerts
|

Adult and Larval Tracheal Systems Exhibit Different Molecular Architectures in Drosophila

Abstract: Knowing the molecular makeup of an organ system is required for its in-depth understanding. We analyzed the molecular repertoire of the adult tracheal system of the fruit fly Drosophila melanogaster using transcriptome studies to advance our knowledge of the adult insect tracheal system. Comparing this to the larval tracheal system revealed several major differences that likely influence organ function. During the transition from larval to adult tracheal system, a shift in the expression of genes responsible f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 69 publications
(79 reference statements)
0
1
0
Order By: Relevance
“…During pupal metamorphosis, airway progenitor cells, the tracheoblasts, give rise to the adult tracheal system by using parts of the larval system as scaffold 51 . Of note, the airway system of adult flies is much more complex than that of larvae 52 . Having shown that development is disturbed in gene-modified flies, we next monitored the lifespan of male and female adult flies until natural death occurred.…”
Section: Resultsmentioning
confidence: 99%
“…During pupal metamorphosis, airway progenitor cells, the tracheoblasts, give rise to the adult tracheal system by using parts of the larval system as scaffold 51 . Of note, the airway system of adult flies is much more complex than that of larvae 52 . Having shown that development is disturbed in gene-modified flies, we next monitored the lifespan of male and female adult flies until natural death occurred.…”
Section: Resultsmentioning
confidence: 99%
“…A role for ELKS in peptide release has been described for insulin secretion in pancreatic β-cells (Ohara-Imaizumi et al, 2019). Yet, peptidergic ecdysis-triggering hormone (ETH) release from the endocrine epitracheal cells also appeared to be BRPindependent (unpublished data), though BRP is expressed by those cells (Bossen et al, 2023).…”
Section: Discussionmentioning
confidence: 97%